Modulation in the Idiom Translation from English to Indonesian in the Novel Rich People Problems - Efendi, Lutfi; Hardjanto, Tofan Dwi (SALEE: Study of Applied Linguistics and English Education, 2023)
Modulation ??is seen as two different points of view in a similar situation. This research describes the modulation in the translation of idioms in the novel Rich People Problems. The material objects of the research were the English novel Rich People Problems and its Indonesian translation. The idioms were in the form of words, phrases, clauses, and sentences found in the novels. The data-collecting process included reading and then underlining them. After the idioms were identified, their meanings were checked and verified using the idiom dictionaries. The idioms were analyzed by using the theory of Makkai (1972) and the modulation theory by Vinay and Darbelnet (1995). Phrasal verb idioms were not dominantly shifted though they are mostly found in the translation of idioms. In addition, modulation can have both narrowing and widening meanings in the target language. On the other hand, modulation mainly occurs in sentences or idioms that take the form of sentences or clauses.